2010
DOI: 10.1021/la101769y
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Chemistry of Dimethyl Disulfide on Copper

Abstract: The surface chemistry of dimethyl disulfide (DMDS) is studied on a Cu(111) single crystal and a polished copper foil in ultrahigh vacuum as a basis for understanding its tribological chemistry using a combination of temperature-programmed desorption (TPD), reflection-absorption infrared spectroscopy (RAIRS), and X-ray photoelectron spectroscopy (XPS). Low-energy electron diffraction reveals that the polished foil becomes ordered on heating in vacuo and displays identical surface chemistry to that found on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 50 publications
(60 reference statements)
6
63
0
Order By: Relevance
“…The width of the silver wire is also indicated DMDS is selected for these experiments for a number of reasons. It reacts rapidly with copper at *100 K via facile cleavage of the S-S bond to deposit thiolate species (CH 3 -S) on the surface, which are stable to *450 K and decompose to desorb methane and deposit sulfur atoms on the surface [14]. The thiolate monolayer is bonded to the surface via the sulfur atom, with the methyl group oriented away from the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The width of the silver wire is also indicated DMDS is selected for these experiments for a number of reasons. It reacts rapidly with copper at *100 K via facile cleavage of the S-S bond to deposit thiolate species (CH 3 -S) on the surface, which are stable to *450 K and decompose to desorb methane and deposit sulfur atoms on the surface [14]. The thiolate monolayer is bonded to the surface via the sulfur atom, with the methyl group oriented away from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…This ensures that there is no change in the nature of the contact region for tribological experiments performed after dosing the surface and produces a *150 lm wide wear track. The copper surface was then exposed to DMDS at 300 K to form a saturated overlayer of methyl thiolate species [14]. Figure 2a, profile I shows the resulting profile across the wear track of the S LMM Auger (with a kinetic energy of 152 eV) peak-to-peak intensity ratioed to that of the copper LMM Auger peak (with a kinetic energy of 920 eV), where the center of the wear track is located at *300 lm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface chemistry of DMDS on copper was studied in UHV using a number of surface-sensitive techniques, including temperature-programmed desorption (TPD), 63 X-ray photoelectron spectroscopy, 62 and reection-absorption infrared spectroscopy (RAIRS). 34 These experiments reveal that DMDS adsorbs molecularly on copper at $80 K, but heating to $200 K causes S-S bond scission to form methyl thiolate (CH 3 -S-) species on the surface. The methyl thiolate species are stable up to $426 K, where they thermally decompose to desorb methane along with some ethylene and ethane.…”
Section: Surface Reactions Of Dimethyl Disulde With Coppermentioning
confidence: 98%
“…However, it has been shown that these clean and annealed copper foils exhibit sufficient order to display distinct low-energy electron diffraction (LEED) patterns indicating that the surface is ordered. [45]…”
Section: Rtmentioning
confidence: 99%